CORRELATION BETWEEN DEGREE OF PROPTOSIS WITH EYE BALL DIMENSION IN GRAVES OPHTHALMOPATHY PATIENT AT WAHIDIN SUDIROHUSODO HOSPITAL MAKASSAR: Oral Presentation - Observational Study - Ophthalmologist - Stephanie Tanjung (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Introduction Hyperthyroidism is one of the cause of Graves’ Ophthalmopathy (GO), which is an autoimmune orbital disease. Clinical manifestations of GO are orbital and periorbital edema, eyelid retraction, eyelid lag in down gaze, restrictive strabismus, compressive optic neuropathy, and keratopathy exposure. We can also find proptosis in GO patient. this happened because the expansion of adipose tissue and muscle at the edge of the orbital bones resulting in increased intraorbital pressure. Protrusion of eyeball can cause changes in the dimensions of the eyeball such as axial length, anterior chamber depth, and cornea curvature. Objective To assess the correlation of degree of proptosis with eyeball dimension in Patients Graves’ Ophthalmopathy. Methods : This research was a cross sectional study. A total of seventeen eyes were proptotic from patient with Graves' ophthalmopathy. They underwent measurement with a Hertel exophthalmometer and optical biometry to record the degree of proptosis, axial length, anterior chamber depth, and cornea curvature. Results : Patient with proptosis in Graves' Ophthalmopathy. This study analysed the degree of proptosis with axial length, anterior chamber depth, and cornea curvature. There is no statistically significant result. Conclusion : There was no correlation between degree of proptosis with axial length, anerior chamber depth, and cornea curvature in patient with Graves’ Ophthalmopathy.